WAYS TO ORGANIZE MUSIC LISTENING ACTIVITIES IN MUSIC CULTURE CLASSES (American Journal of Pedagogical and Educational Research, 2023)
This article explores the importance of organizing music listening activities in music culture classes. It highlights the benefits of structured approaches, such as curated playlists, thematic exploration, historical chronology, and active listening techniques. The article emphasizes the role of organization in fostering student engagement, critical thinking, and appreciation for diverse musical genres.